Hybrid firefly bat algorithm (HFBA)–based network security policy enforcement for PSA. (11th July 2018) - Sureshkumar, Thathan; Lingaraj, Mani; Anand, Bojan; Premkumar, Thathan
Summary: Network operators heavily depend on security services to secure their information technology infrastructures. On the other hand, due to the complexity of security policies, it is not appropriate to straightforwardly use previous pathwise enforcement approaches. In this paper, the enforcement problem of the security policy on middleboxes is formulated as a weighted K set covering problem that requires a policy space analysis tool. This tool is intended to be supported on range‐represented hyperrectangles, which are tagged using a prioritized R‐tree. This methodological work initially evaluates the topological features of diverse types of policies. Hybrid firefly bat algorithm–supported heuristic information shows the inherent difficulties of security policies and provides direction for the design of the enforcement algorithm. At the same time, a scopewise policy enforcement procedure is proposed, which requires a moderate number of enforcement network nodes for organizing the various policy subsets in a greedy manner. Our results demonstrate that the proposed hybrid firefly bat algorithm with policy space analysis offer greatly improved outcomes in terms of the rule overhead, network security, packet delivery ratio, packet loss ratio, and time efficiency above the set operations of the security policy. Abstract : Hybrid firefly bat algorithm–supported heuristic information shows the inherent difficulties of security policies and provides direction for the design of the enforcement algorithm. At the same time, a scopewise policy enforcement procedure is proposed, which requires a moderate number of enforcement network nodes for organizing the various policy subsets in a greedy manner. Our results demonstrate that the proposed hybrid firefly bat algorithm with policy space analysis offer greatly improved outcomes in terms of the rule overhead, network security, packet delivery ratio, packet loss ratio, and time efficiency above the set operations of the security policy.